COVID-19, Misinformation and Communication Studies: A Systematic Review of the Infodemic - Oğuz Kuş; İlknur Doğu Öztürk (Connectist Istanbul University Journal of Communication Sciences)
This study aims to structure the available body of knowledge relating to the infodemic by means of a systematic review and explore it in a multidimensional manner by taking into account the speed of the propagation of misinformation, its fast-changing nature and effects. The study also aims to present the interaction between the field of communication and other fields of study within the framework of the ongoing infodemic. The studies for systematic review were gathered from internationally known scientific databases, namely the Web of Science Core Collection and Google Scholar, over two stages. A total of 46 studies were included in this systematic review. This study utilized an inductive research approach for systematic review. Using this approach, the authors’ identified the reasons for the propagation of misinformation during the COVID-19 pandemic in these papers. The authors also identified the effects of this misinformation, the methods of individuals, official and non-official actors to combat misinformation, the cultural factors and legal measures for combating misinformation, and the recommendations related to traditional media, the new media and other verification structures. The studies conducted in the field of communication were predominantly cited in studies conducted within Communication and Health & Health Care Sciences fields. A notable observation made in this study was that studies which focused on combating misinformation were cited more than other studies reviewed.